Decolonizing or Re-colonizing? Community members’ perspectives of global service learning programs - Noel Habashy; Nicole Webster; Carter A. Hunt (World Development Sustainability)
Global service learning (GSL) sits at the interdisciplinary intersection of international development and study abroad, with visiting university students engaging in community development projects. Many GSL programs assert they contribute to the development of local communities, and promote greater cultural understanding for student participants. However, GSL can be a setting where unequal power dynamics are reinforced, and local community interests and histories are overlooked or patronized. Unfortunately, despite the growing emphasis on evaluation among international development and education abroad programs, few empirical studies exist to examine the perspectives of local communities that host GSL programs. The purpose of this research is to assess community power dynamics as affected by GSL using a comparative case study of communities in Costa Rica and Kenya. A rapid ethnographic approach yielded qualitative data via semi-structured interviews, archival sources, and participant observation. A comparative analysis of these data highlights the ways local residents engage with service learning programs, opportunities provided to residents with access to programs, and obstacles to a more ethical community development. Our study finds residents in these cases value relationships with visiting students and infrastructure development within a community, however, they lament instances where students and organizations do not listen to their perspectives. Our findings will be relevant to the design and implementation of the thousands of education abroad and international volunteer programs taking place annually. Without seeking insights from local residents, global service learning may be reinforcing colonialistic patterns.